Real-Time Behaviour of Dredged Slurry Treated by Air-Booster Vacuum Consolidation - Kang Yao; Da Cheng; Junhui Sheng; Li Shi; Lijian Hu; Yanming Yu (Applied Sciences, 2023)
The air-booster vacuum preloading method has been applied to slurry ground improvement. It is based on the conventional vacuum preloading method but with an additional injection of pressurised air into the soil via pre-installed conductors. The drainage effect of air-booster vacuum preloading has been demonstrated by past studies; however, direct observations of the real-time behaviour of slurries subjected to boosted air remain lacking. This study used a combined monitoring technique that included particle image velocimetry, pore water/air pressure gauges, a vortex flowmeter and an electronic balance to conduct a laboratory test of air-booster vacuum consolidation of dredged slurry. The tests allowed analyses of (1) the real-time displacement field of the slurry, (2) the pressure–flux relationship of the pressurised air, and (3) the pore water pressure responses during air boosting. The first aspect allowed direct observation of small-crack initialisation and propagation during pressurisation; while the latter two confirmed the crack initiation based on drops in air and pore water pressures. The measured crack initiation pressure was verified by comparison with theoretical predictions. The results demonstrate that pressurised air induces cracks in soil, which promote the drainage consolidation of dredged slurry.